The Challenges of COVID-19 with Obesity-Related Cancers - Dalamaga, Maria; Nasiri-Ansari, Narjes; Spyrou, Nikolaos (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint emphasizes the perspectives and challenges surrounding COVID-19 and obesity-related cancers, including but not limited to the risk factors of severe COVID-19 in cancer patients; the complications of COVID-19 in cancer patients; the challenges in cancer treatment and surgery; guidelines for cancer care during COVID-19; delayed diagnosis and suboptimal cancer management; the impact of COVID-19 on cancer screening, early diagnosis and cancer presentation; immune response after SARS-CoV-2 infection and vaccination in cancer patients; psychological distress among cancer survivors; telehealth in cancer care; the role of diet and nutraceuticals in the prevention of severe COVID-19 and cancer; and the effects of COVID-19 pandemic on cancer research.